Ex situ collections and their potential for the restoration of extinct plants. Issue 2 (19th September 2019) - Abeli, Thomas; Dalrymple, Sarah; Godefroid, Sandrine; Mondoni, Andrea; Müller, Jonas V.; Rossi, Graziano; Orsenigo, Simone
Abstract: The alarming current and predicted species extinction rates have galvanized conservationists in their efforts to avoid future biodiversity losses, but for species extinct in the wild, few options exist. We posed the questions, can these species be restored, and, if so, what role can ex situ plant collections (i.e., botanic gardens, germplasm banks, herbaria) play in the recovery of plant genetic diversity? We reviewed the relevant literature to assess the feasibility of recovering lost plant genetic diversity with using ex situ material and the probability of survival of subsequent translocations. Thirteen attempts to recover species extinct in the wild were found, most of which used material preserved in botanic gardens (12) and seed banks (2). One case of a locally extirpated population was recovered from herbarium material. Eight (60%) of these cases were successful or partially successful translocations of the focal species or population; the other 5 failed or it was too early to determine the outcome. Limiting factors of the use of ex situ source material for the restoration of plant genetic diversity in the wild include the scarcity of source material, low viability and reduced longevity of the material, low genetic variation, lack of evolution (especially for material stored in germplasm banks and herbaria), and socioeconomic factors. However, modern collecting practices present opportunities for plant conservation, such as improved collecting protocols and improved cultivation and storage conditions. Our findings suggest that all types of ex situ collections may contribute effectively to plant species conservation if their use is informed by a thorough understanding of the aforementioned problems. We conclude that the recovery of plant species currently classified as extinct in the wild is not 100% successful, and the possibility of successful reintroduction should not be used to justify insufficient in situ conservation. Abstract : Article impact statement : Ex situ collections avoid loss of plant diversity, but recovering lost genetic diversity from ex situ material only is highly challenging. Abstract : Colecciones Ex Situ y su Potencial para la Restauración de Plantas Extintas Resumen: Las alarmantes tasas de extinción actuales y pronosticadas han incitado a los conservacionistas a esforzarse para evitar las futuras pérdidas de biodiversidad, pero para las especies que ya se encuentran extintas en vida silvestre existen pocas opciones. Nos preguntamos si estas especies pueden ser restauradas, y de ser así, qué papel pueden desempeñar las colecciones ex situ de plantas (es decir, jardines botánicos, bancos de germoplasma, herbarios) en la recuperación de la diversidad genética de las plantas. Revisamos la literatura relevante para evaluar la factibilidad de la recuperación de la diversidad genética perdida y la probabilidad de supervivencia subsecuente de las reubicaciones. Encontramos 13 intentos por recuperar especies extintas en vida silvestre, la mayoría de los cuales usó material preservado en jardines botánicos (12) y en bancos de semillas (2). También hubo un caso de una población eliminada localmente que fue recuperada con material de un herbario. Ocho (60%) de estos casos fueron reubicaciones exitosas o parcialmente exitosas de la especie o población focal; los otros cinco fallaron o era demasiado pronto para poder determinar el resultado. Los factores que limitan el uso de material proveniente de colecciones ex situ para la restauración de la diversidad genética de las plantas en vida silvestre incluyen la escasez de material original, la baja viabilidad y la longevidad reducida del material, la baja variación genética, la falta de evolución (especialmente para el material almacenado en herbarios y bancos de germoplasma) y los factores socioeconómicos. A pesar de esto, las prácticas modernas de colección representan una oportunidad para la conservación de las plantas, como los protocolos mejorados de recolección y las condiciones acrecentadas de cultivo y almacenamiento. Nuestros hallazgos sugieren que todos los tipos de colecciones ex situ pueden contribuir efectivamente a la conservación de especies de plantas si su uso está respaldado por un entendimiento a fondo de los problemas antes mencionados. Concluimos que la recuperación de especies de plantas que actualmente están clasificadas como extintas en vida silvestre no es 100% exitosa y que la posibilidad de una reintroducción exitosa no debería utilizarse para justificar una conservación in situ insuficiente.